Ionic indium(iii) chloride hybrids incorporating a 2, 2′-bipyrimidine ligand: studies on photoluminescence and structural transformation. Issue 44 (4th November 2021) - Jin, Jian-Ce; Zhuang, Ting-Hui; Lin, Yang-Peng; Lin, Bing-Ye; Jiang, Jiang; Du, Ke-Zhao; Huang, Xiao-Ying
Abstract : The first three indium(iii ) chloride hybrids composed of a 2, 2′-bipyrimidine-incorporating haloindium(iii ) anion and ionic liquid cations were synthesized and structurally studied, which show structural transformation and photoluminescence switching. Abstract : Although luminescent indium(iii ) based halide perovskites have been widely investigated, the study of emissive indium(iii ) halide hybrids is limited. Three indium(iii ) chloride hybrids based on a bpym ligand were synthesized, namely [EPy]2 [InCl4 (bpym)InCl4 ]·DMF (1 ), [EPy]2 [InCl4 (bpym)InCl4 ] (2 ), and [BPy]2 [InCl4 (bpym)InCl4 ] (3 ) (EPy = N -ethylpyridinium; BPy = N -butylpyridinium; bpym = 2, 2′-bipyrimidine). They all exhibit a zero-dimensional structure, in which the ligand bpym interconnects two [InCl4 ] − to form a [InCl4 (bpym)InCl4 ] 2− anion that is further charge-compensated by the corresponding pyridinium cations. This is the first time using bpym to coordinate with an In atom. At 298 K, 1 exhibits a weak emission at 600 nm while 2 and 3 exhibit emissions peaking at 500 nm and 540 nm, respectively. Interestingly, the DMF solvent molecule in 1 can be removed by heating, thus resulting in the structural transformation of 1 into 2 together with a photoluminescence (PL) change. Density functional theory (DFT) calculations confirm that halogen-to-ligand charge-transfer (HLCT) occurs in the emission process. To the best of our knowledge, this is the first report on PL of ionic indium(iii ) halide hybrids incorporating organic ligands.